Assistance in Introducing Operational Systems Along with Administration and Financial Reporting in Accordance with Tri-Nga Teachings (Ngerti, Ngroso, Nglakoni) - Suyanto, Suyanto; Pratama , Yhoga Heru; Putri, Fuadhillah; Rokhim, Abdul (IMPACTS: International Journal of Empowerment and Community Services, 2025)
Purpose This community service program aims to assist the Budi Pekerti Luhur Women's Sharia Savings and Loan Cooperative (KSPPS-P BUPELUR) in understanding its operational systems, preparing financial reports, and improving cooperative administration. During its eight years of operation, this cooperative still faces a number of challenges in financial management, such as manual financial recording, discrepancies between records and actual transactions, and errors in recording depreciation and amortization that do not match the amount of assets owned. In addition, the cooperative's management also experiences difficulties in bookkeeping and archiving financial documents. Methods - In this community service program, various methods will be used to provide solutions to the problems faced, including lectures, interactive discussions, independent assignments, role plays, and evaluations. These methods are expected to improve participants' understanding and skills in cooperative financial management. Result and discussions - The community service team will provide education and training covering various important aspects of the cooperative system, namely: Introduction to the cooperative operational system, Cooperative member registration procedures, Management of savings transactions, Management of financing transactions, Preparation of cooperative journals, Preparation of general journals, Preparation of financial reports, Management and regulation of administrative systems. The material presented in this training will refer to the Tri Nga philosophy, namely Ngerti (understanding), Ngrasa (feeling), and Nglakoni (doing). This approach aims to ensure that participants not only gain theoretical understanding, but also feel the importance of good financial management and apply it in their daily practices. Conclusion - Through this program, participants are expected to gain a better understanding of preparing financial statements based on Financial Accounting Standards for Private Entities (SAK EP). In addition, they will also be guided in recording depreciation and amortization of assets more accurately and improving their skills in bookkeeping and archiving financial documents systematically using digital technology, such as Google Drive and spreadsheets. Thus, cooperatives can manage their finances more efficiently, transparently, and in accordance with applicable accounting standards.